2015
DOI: 10.1073/pnas.1424705112
|View full text |Cite
|
Sign up to set email alerts
|

BEND3 represses rDNA transcription by stabilizing a NoRC component via USP21 deubiquitinase

Abstract: Ribosome biogenesis dictates the translational capacity of cells. Several mechanisms establish and maintain transcriptional output from eukaryotic ribosomal DNA (rDNA) loci. rDNA silencing is one such mechanism that ensures the inactivity and hence the maintenance of a silenced state of a subset of rRNA gene copies. Whereas oncogenic agents stimulate rRNA gene transcription, tumor suppressors decrease rRNA gene transcription. We demonstrate in mammalian cells that BANP, E5R, and Nac1 (BEN) domain 3 (BEND3), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…In our recent work, we show that SUMOylation of BEND3 is important for the stability of NoRC. 8 We find that Tip5 undergoes ubiquitin-mediated degradation in the presence of a BEND3 sumo double mutant (BEND3-SDM) but not in the presence of the wild type protein (BEND3-WT). Tip5 is deubiquitinated in the presence of BEND3-WT, thereby stabilizing and preventing its degradation.…”
Section: Role Of Bend3 Sumoylation In Gene Regulationmentioning
confidence: 81%
See 3 more Smart Citations
“…In our recent work, we show that SUMOylation of BEND3 is important for the stability of NoRC. 8 We find that Tip5 undergoes ubiquitin-mediated degradation in the presence of a BEND3 sumo double mutant (BEND3-SDM) but not in the presence of the wild type protein (BEND3-WT). Tip5 is deubiquitinated in the presence of BEND3-WT, thereby stabilizing and preventing its degradation.…”
Section: Role Of Bend3 Sumoylation In Gene Regulationmentioning
confidence: 81%
“…27 BEN domain has been shown to posses sequence specific DNA binding activity 28,29 and, indeed, we have also shown that BEND3 can directly bind to DNA as well. 8 Apart from BEND3, the only other BEN domain-containing protein in mammals studied so far is BEND6 which is a BEN-solo domain protein involved in Notch signaling. 29 We have shown that BEND3, a quadruple BEN domain-containing protein, plays an important role in rDNA silencing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, 5 µg of IgG was used to pull 50 µg of cross-linked and sheared chromatin as a control. Pol II ChIP was performed as reported earlier ( Khan et al, 2015 ). Briefly, cells were fixed using freshly prepared 1% Formaldehyde solution for ten minutes at room temperature followed by quenching with 0.125 M Glycine solution.…”
Section: Methodsmentioning
confidence: 99%